EFFECT OF GRADED LEVELS OF DIETARY RAW SESAME SEEDS ON GROWTH PERFORMANCE, SERUM BIOCHEMISTRY AND NUTRIENT DIGESTIBILITY OF BROILER CHICKENS. - & et al., Passi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This experiment was conducted to investigate the effect of dietary inclusion of raw sesame seeds (RSS) on performance, serum biochemistry, carcass characteristics and digestive physiology of broiler chickens between hatch and 35 days of age. Three inclusion levels (0, 5 or 10 g/kg) of RSS were included in the starter, grower and finisher diets on either wheat- or maize-based diets. At first 10 days, birds tended (P < 0.06) to eat more with increasing concentrations of RSS. At day 35, there was an interaction (P < 0.05) between the level of RSS and the grain, depressing the serum cholesterol in birds that received RSS at the medium concentration in wheat-based diets. The RSS and the grain tended (P = 0.056) to interact arising from the relatively higher triglycerides in birds on wheat-based diets supplemented with medium level of RSS. There was an interaction (P < 0.05) between the level of RSS and the grain, indicating the lowest gross energy digestibility in the birds that received RSS at the highest concentration in maize-base diets. Increasing concentrations of RSS in the diets decreased (P < 0.05) the apparent digestibility of protein and nitrogen at 35 days of age. The results provided evidence that beyond providing nutrients for growth, sesame seeds can maintain feed intake and regulate the cholesterol level.